High actuated performance MWCNT/Ecoflex dielectric elastomer actuators based on layer-by-layer structure. (October 2019) - Xu, Zewang; Zheng, Shaodi; Wu, Xiaotian; Liu, Zhengying; Bao, Ruiying; Yang, Wei; Yang, Mingbo
Abstract: A layer-by-layer structure was constructed by alternately arranging conductive layers and insulating layers in a silicone dielectric elastomer (Ecoflex) to largely improve the actuated strain at a low electric field. In the electric field environment, the insulating layer blocks the transmission channel of electrons in the adjacent conductive layer, so the interfaces of adjacent conductive layers and insulating layers can accumulate and store a large number of charges, thereby greatly increasing the dielectric constant of the material. Meanwhile, the individual conductive layers are separated by an insulating layer to avoid causing large conductance losses. A high actuated strain (20.33%) at a relatively low electric field (12.5 kV mm −1 ) and good cyclic stability are obtained on the actuator without any pre-strain. These results demonstrate that our research provides a simple and effective method to significantly improve the actuated strain at a low electric field of DE and promote its practical application.